Design of an eco-friendly vegetable/flower bed for the HDB balcony - Chang, Cheng Hung. (2011)
The purpose of designing an ecology-friendly flower bed in HDB flat is mainly to provide a more convenient method for folks in the city to grow plants of their choices through a simple way.